PENGARUH STANDAR OPERASIONAL PROSEDUR (SOP) DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT. YUSEN LOGISTICS SOLUTIONS INDONESIA - Mustopa Hidayattulloh; Muhammad Ridwan (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2019)
The purpose of this study was to determine how much influence the Standard Operating Procedures (SOP) and Supervision of Employee Performance at PT. Yusen Logistics Solutions Indonesia, both partially and simultaneously. Data analysis in this study used the SPSS 22 program, namely by using the classic assumption test, simple and multiple regression analysis, simple and multiple correlation analysis, and hypothesis testing and f test. Data were collected using a questionnaire. The results showed a positive and significant effect between standard operating procedures (SOP) on employee performance partially, with a significance value of 0.020 <0.05 and a calculated T value of 2.394> T table 1.676. While supervision of employee performance partially has a significance value of 0.999> 0.05, a significance value of greater than 0.05 and a calculated T value of 0.001 <T table 1.676 so that it does not have a significant effect. From the results of simultaneous calculations (together) between variables Standard Operating Procedure (SOP) and Supervision of Employee Performance has a value of 0.004 <0.05 and F value of 6.061> F table 3.18 means that the data shows that there is a positive influence and significant .. R Square value of 0.195, this implies that the influence given by the variable Standard Operating Procedures (SOP) and Supervision of Employee Performance by 19.5%.